THE EXTENT of SEED PREDATION BY BRUCHINE BEETLES (COLEOPTERA: CHRYSOMELIDAE: BRUCHINAE) IN A HETEROGENEOUS LANDSCAPE IN SOUTHEASTERN BRAZIL - Rodrigues, Ligia M. S. [UNESP]; Viana, Jessica H.; Ribeiro-Costa, Cibele S.; Rossi, Marcelo N. (Coleopterists Soc, 2012)
In this study, seed predation rates imposed by bruchines and the composition of bruchine species and their host plants were assessed in a heterogeneous landscape in southeastern Brazil. Fruits were collected from 49 plants from 16 species belonging to four families, primarily Fabaceae. The five bruchine species collected emerged from four plant species as follows: Acanthoscelides macrophthalmus (Schaeffer) from Leucaena leucocephala (Lamarck) de Wit, Acanthoscelides sp. from Senna hirsuta (L.) Irwin and Barneby, Ctenocolum podagricus (F.) from Lonchocarpus muehlbergianus Hassler, and Gibbobruchus polycoccus (Fahraeus) and Gibbobruchus speculifer (Gyllenhal) from Bauhinia forficata Link. Bauhinia forficata is here recorded for the first time as a host for G. polycoccus. Only 1/4 of the local flora that was surveyed hosted bruchines. Bruchine and plant species composition varied among habitats, with most beetles found in plants located in the most disturbed habitat. Because of the economic importance of L. leucocephala in the tropics, we compared germination percentages between attacked and unattacked seeds of this species. The unattacked seeds had an average germination rate of 59%, and none of the attacked seeds germinated, showing that the germination of L. leucocephala seeds was drastically affected by predation.
Keywords: ecology; Neotropics; predispersal seed predation; seed germination; semideciduous seasonal forest; seed beetles